Pengaruh Program Pemerintah Terhadap Pengeluaran Rumah Tangga Pertanian di Sumatera Barat - Ali Asy'ari; Isra Yeni (Universitas Negeri Padang, 2025)
AbstractThis study aims to analyze the impact of government programs on agricultural household expenditures in West Sumatra. Utilizing data from the 2023 National Socioeconomic Survey (Susenas), the research employs multiple linear regression methods to evaluate the relationship between independent variables government programs, credit access, and internet access and expenditures on food, non-food, and total agricultural household expenses. The analysis results indicate that all independent variables have a positive and significant effect on household expenditures. Government programs and credit access improve food and non-food expenditures, while internet access has a more substantial impact on total expenditures. These findings underscore the importance of government intervention in enhancing the welfare of farming households, especially in facing complex economic challenges. The study offers recommendations for the government to enhance the effectiveness of social assistance programs and access to resources that support the welfare of farming communities in West Sumatra.AbstrakPenelitian ini bertujuan untuk menganalisis pengaruh program pemerintah terhadap pengeluaran rumah tangga pertanian di Sumatera Barat. Menggunakan data dari Survei Sosial Ekonomi Nasional (Susenas) 2023, penelitian ini mengadopsi metode regresi linear berganda untuk mengevaluasi hubungan antara variabel independen, yaitu program pemerintah, akses kredit, dan akses internet, terhadap pengeluaran makanan, non-makanan, dan total rumah tangga pertanian. Hasil analisis menunjukkan bahwa semua variabel independen berpengaruh positif dan signifikan terhadap pengeluaran rumah tangga. Program pemerintah dan akses kredit meningkatkan pengeluaran makanan dan non-makanan, sedangkan akses internet memberikan dampak yang lebih besar terhadap pengeluaran total. Temuan ini menegaskan pentingnya intervensi pemerintah dalam meningkatkan kesejahteraan rumah tangga petani, terutama dalam menghadapi tantangan ekonomi yang kompleks. Penelitian ini memberikan rekomendasi bagi pemerintah untuk meningkatkan efektivitas program bantuan sosial dan akses terhadap sumber daya yang mendukung kesejahteraan masyarakat petani di Sumatera Barat.